School procedural justice and being pushed out: examining the intersection of sex and race/ethnicity. Issue 4 (3rd July 2020) - Varela, Kay S.; King, Sanna; Peguero, Anthony A.; Rusoja, Alicia
Abstract: There is a growing body of research that explores how school punishment practices are disrupting educational progress. It is also known that educational success and failure are linked to sex and racial/ethnic inequalities. What remains less known is how school punishment and student perceptions of just and fair punishment practices are related to sex and racial/ethnic disparities, specifically with the likelihood of being pushed out. This study utilizes multilevel analyses, drawing from the Education Longitudinal Study of 2002, to examine the impact school procedural justice has on being pushed out for male and female racial/ethnic minority students. The findings indicate that fair and just school procedural justice practices moderate the relationship between punishment and being pushed out. It also appears, however, male and female racial/ethnic minority students have increased odds of being punished, as well as have poor perceptions their school's procedural justice. Even though improving school procedural justice could minimize the risk of being pushed out for male and female racial/ethnic minority students, the negative educational effect of being disciplined remains strong.